Progress in artificial intelligence and pattern recognition : 6th International Workshop, IWAIPR 2018, Havana, Cuba, September 24-26, 2018, Proceedings /: 6th International Workshop, IWAIPR 2018, Havana, Cuba, September 24-26, 2018, Proceedings. (2018) - Unknown
No abstract available